Naked money : a revealing look at what it is and why it matters - Wheelan, Charles J. (W.W. Norton & Company, 2016)
"The best-selling author of Naked Statistics and Naked Economics explores the colorful world of money and banking to answer such questions as how money creation is used to counter financial crises, why the shared European currency has caused so much trouble and how Bitcoin will impact the future,"--NoveList.